2011
DOI: 10.1016/j.neuroimage.2011.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Reduced striatal volume in cocaine-dependent patients

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 66 publications
9
94
4
1
Order By: Relevance
“…However, scant evidence exists for a neuroanatomic correlation of these clinical differences. Authors of some studies (15)(16)(17) primarily have recruited men to exclude the confounding effects of sex, and other investigators (2,18,19) have not included sex as a factor in their analyses of gray matter in patients with stimulant dependence. In fact, to our knowledge, only two studies (20,21) have included descriptions of structural differences between the sexes in patients with stimulant dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, scant evidence exists for a neuroanatomic correlation of these clinical differences. Authors of some studies (15)(16)(17) primarily have recruited men to exclude the confounding effects of sex, and other investigators (2,18,19) have not included sex as a factor in their analyses of gray matter in patients with stimulant dependence. In fact, to our knowledge, only two studies (20,21) have included descriptions of structural differences between the sexes in patients with stimulant dependence.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Ersche et al (2) studied 494 subjects with stimulant dependence (79% men) and 428 healthy control subjects (69% men) and reported smaller GMV in those with stimulant dependence than in control subjects in the insulae, inferior frontal gyrus, anterior cingulate gyrus, and anterior thalamus; however, the authors did not comment on the effect of sex on the results. Authors of other studies of drug effects on brain morphometry excluded women (15)(16)(17), which shows the need for prospective studies to investigate the effects of sex. Here we report significant neuroanatomical sexual dimorphism in the largest prospective sample of patients with stimulant dependence evaluated according to sex and group to date.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the pattern of smaller GM volumes observed with in utero exposure is similar to that reported in adults with chronic cocaine use. Cocaine-dependent adults exhibit GM loss in frontal regions including orbital frontal, dorsal lateral prefrontal cortex, inferior, medial and superior frontal gyri and premotor cortex, with greater lifetime exposure resulting in greater reductions (Franklin et al 2002; Sim et al 2007; Alia-Klein et al 2011; Barros-Loscertales et al 2011; Ersche et al 2011; Moreno-Lopez et al 2012). These deficits are accompanied by impairment in cognitive skills including decision-making, memory, nonverbal problem solving, response inhibition, impulsivity, spatial processing and reaction time tasks (Fein et al 2002; Lane et al 2010)(62).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of this brain volume reduction seems to increase as a function of the number of years of drug use [41,47]. Among these studies, nearly all of those that allowed for inspection of the subdivisions of IC found differences in PIC.…”
Section: Evidence From Neuroimaging Studiesmentioning
confidence: 99%